UN WOMEN DAN KAMPANYE ORANGE THE WORLD DALAM MERESPONS KEKERASAN BERBASIS GENDER DI INDONESIA - Farhan, Muhammad; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Gender-based violence is an issue that remains a serious concern in Indonesia, where women are often vulnerable victims. Indonesia as a country that ratified CEDAW is experiencing an upward trend in cases of violence against women. To address this issue, the UN through UN Women has created various initiatives, including the Orange the World Campaign which aims to raise public awareness and reduce gender-based violence. UN Women, as a UN entity that focuses on gender equality, plays an important role in supporting the implementation of this campaign in Indonesia. This research aims to explore UN Women's function in helping to address gender-based violence in Indonesia through the Orange the World Campaign. The research method used is qualitative with data collection techniques through document analysis and in-depth interviews with UN Women Indonesia and Komnas Perempuan.. This research uses a liberalism perspective to explain that relationships between individuals, groups and organizations from different countries will create cooperative relationships. Intergovernmental organization theory is used to analyze the implementation of UN Women Indonesia's function as an IGO in the Orange the World Campaign. The results of this study provide a deeper understanding of UN Women's efforts to address gender-based violence in Indonesia through a holistic and sustainable campaign. The research findings show that UN Women carries out its information, forum, and operational functions to respond to gender-based violence in Indonesia through this campaign in the 2020-2022 period through various programs that are aligned with UN Women Indonesia's two work focuses, namely ending violence against women and women, peace, and security. Keywords: Gender-based violence, UN Women, Orange the World Campaign, Indonesia